Analysis of Stable Flight of Poltekad Eagle Drone Using ANSYS Method - Nur Rachman Supadmana Muda; Nugraha Gumilar; Suko Wiyanto; Fajar Kholid (Postgraduate, University of Mataram, 2024)
The purpose of this study was to analyze the movement of the wings of a self-made eagle drone using the ANSYS method. The drone analyzed for the wing type moves to fly by being thrown when the brushless motor throttle moves the flapping of the wings at maximum rotation. The aerodynamic model used for data analysis in this paper is optimized to determine and improve the operational performance of the wings of eagle drones, especially in terms of stability and flight time. These two aspects are very important to determine the efficiency of drone performance. The method used for simulation analysis uses ANSYS 13. In the next step, the numerical results will be compared with the results during the experimental flight process. The conclusion of this study presents the main results of the simulation, namely numerical magnitude, main flight coefficient and flight time that affect stable flight efficiency.